Efforts to reduce truancy behavior through group guidance services for class xi-otkp students at state vocational high school 1 hilimegai - Erika Halawa (Institute of Accounting Research and Novation (IARN), 2023)
The purpose of this BK class action research is to find out whether group guidance services can reduce truant behavior in Class XI-OTKP Students at Hilimegai 1 State Vocational High School. The subjects of this research were students in class Determination of classes was based on the level of problems they had in accordance with the results of discussions with fellow teachers carried out before the research, namely that all students in the class had played truant at a low rate and the frequency ranged from 9 to 15 times. The results of research on reducing truancy behavior through group guidance services for students in class . 2) Reducing students' truant behavior with treatment in the form of group guidance services, obtained fairly good criteria (62.86%) in cycle I. After receiving group guidance, the criteria increased to high (85.71%) in cycle II, thus, there was an increase amounting to 22.85%. This improvement includes positive aspects of self-adjustment and negative truant behavior. So it can be concluded that group guidance services are able to increase the reduction of students' truant behavior at school. 3) The reduction in truant behavior shows a significant increase after receiving group guidance services, which means group guidance can increase the reduction in truancy behavior at school.